Resin composition and molded article containing the same

The resin composition, comprising cellulose powder, maleic anhydride-modified polyolefin, olefin elastomer, and low-density polyethylene, addresses the issues of yellowing and limited molding methods in existing resin compositions by enabling low-temperature manufacturing without a side feeder and accommodating various molding techniques, resulting in improved toughness and rigidity of the molded product.

JP2025059039APending Publication Date: 2025-04-09C I TAKIRON CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024166370
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-27
Filing Date
2024-09-25
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Existing resin compositions face issues with yellowing and unusual odors when manufactured without a side feeder, and they are not suitable for precision molding or blow molding due to their hard nature and limited molding methods.

Method used

A resin composition containing 50 to 70 parts by mass of cellulose powder, 0.5 to 8 parts by mass of maleic anhydride-modified polyolefin, 5 to 20 parts by mass of olefin elastomer, and 12 to 45 parts by mass of low-density polyethylene, which can be easily manufactured at a relatively low temperature without using a side feeder, accommodating various molding methods.

Benefits of technology

The resin composition can be easily manufactured at a relatively low temperature without using a side feeder, reducing the risk of yellowing and unusual odors, and can accommodate various molding methods, resulting in a molded product with improved toughness and rigidity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059039000001_ABST
    Figure 2025059039000001_ABST
Patent Text Reader

Abstract

To provide a resin composition that enables easy production at relatively low temperature without the use of a side feeder, reduces the risk of yellowing and unpleasant odors, and is compatible with various molding methods, as well as a molded article containing the resin composition.SOLUTION: Provided is a resin composition containing cellulose powder. When the total amount of the resin composition is 100 pts.mass, it contains 50 to 70 pts.mass of the cellulose powder, 0.5 to 8 pts.mass of a maleic anhydride-modified polyolefin, 5 to 20 pts.mass of an olefin-based elastomer, and 12 to 45 pts.mass of low-density polyethylene (A). The cellulose powder has an average particle diameter (D50) of 6 μm or more and 24 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition containing cellulose powder and a molded article containing the resin composition. [Background technology]

[0002] In recent years, waste from synthetic resin products, including the problem of marine plastic waste, has come to be seen as a problem. Therefore, there is a demand for reducing the amount of synthetic resin used by converting at least a portion of the raw materials used in synthetic resin products, particularly those that are discarded after use, to raw materials other than synthetic resin.

[0003] Examples of raw materials other than synthetic resins include cellulose materials such as paper. These cellulose materials are inexpensive and have excellent recyclability, and are therefore widely used as reinforcing materials for thermoplastic resins and elastomers, which are used as molding materials for films, etc. Since cellulose materials are biomass materials, blending these cellulose materials with synthetic resin products can result in more environmentally friendly products.

[0004] As a resin composition containing such a cellulose material, for example, a resin composition containing 20 to 70 parts by mass of cellulose powder (fine paper powder) having an average particle size of 10 to 100 μm and 30 to 80 parts by mass of a thermoplastic resin such as polypropylene, the total of the cellulose powder and the thermoplastic resin being 100 parts by mass, has been proposed. It is described that by using such a resin composition, a resin composition having good fluidity and suitable as a material for molding can be obtained (for example, see Patent Document 1).

[0005] As a molded product containing a cellulose material, for example, a bag film has been proposed that contains a fiber-resin mixed composition containing 10-40% by mass of vegetable fiber, 10-40% by mass of polypropylene, and 20-80% by mass of polyethylene, and has a film thickness of 30-180 μm. With regard to the bag film and its manufacturing method, it is described that a film containing vegetable fiber, which is a component of paper, and suitable for forming bags can be obtained (for example, see Patent Document 2). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2013-6411 A [Patent Document 2] WO2022 / 064772 publication Summary of the Invention [Problem to be solved by the invention]

[0007] However, the resin composition of Patent Document 1 has a problem that yellowing and unpleasant odors may occur if a side feeder is not used during production. In addition, since the resin composition is based on polypropylene, it is hard and not suitable for precision molding or blow molding, and there is a problem that the molding method and the molded product are limited.

[0008] Furthermore, the molded article and its manufacturing method of Patent Document 2 have a problem in that the molding temperature is as high as 191° C., and depending on the molding machine used, yellowing or generation of an unpleasant odor may occur. Also, the composition described in this document has a problem in that molding is substantially difficult when the molding temperature is lowered to 160° C. (See Comparative Example 1 in Table 1 below).

[0009] Therefore, the present invention has been made in consideration of the above-mentioned problems, and an object of the present invention is to provide a resin composition that can be easily produced at a relatively low temperature without using a side feeder, has little risk of yellowing or generating an unpleasant odor, and is further applicable to various molding methods, and a molded article using the same. [Means for solving the problem]

[0010] In order to achieve the above object, the resin composition of the present invention is a resin composition containing cellulose powder, and is characterized in that, when the entire resin composition is 100 parts by mass, it contains 50 to 70 parts by mass of the cellulose powder, 0.5 to 8 parts by mass of a maleic anhydride modified polyolefin, 5 to 20 parts by mass of an olefin-based elastomer, and 12 to 45 parts by mass of a low-density polyethylene (A), and the average particle diameter (D50) of the cellulose powder is 6 μm or more and 24 μm or less. Effect of the Invention

[0011] According to the present invention, it is possible to provide a resin composition which can be easily produced at a relatively low temperature without using a side feeder, has a low risk of yellowing or generating an unpleasant odor, and is further suitable for use in a variety of molding methods, and a molded article using the same. [Brief description of the drawings]

[0012] [Figure 1] 1 is a digital microscope image of the surfaces of the molded articles of Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The resin composition of the present invention will be specifically described below. Note that the present invention is not limited to the following embodiments, and can be appropriately modified and applied within the scope of the present invention.

[0014] ≪Resin composition≫ The resin composition of the present invention contains cellulose powder, maleic anhydride modified polyolefin (hereinafter sometimes referred to as "MA-PO"), an olefin-based elastomer such as a propylene-based elastomer, and a low-density polyethylene (A). The resin composition may further contain other components as necessary.

[0015] The resin composition of the present invention is preferably, but not limited to, in the form of a masterbatch, preferably in the form of pellets as a masterbatch, which allows smooth feeding from a hopper to a screw in a process using an extruder, making it possible to handle molded products with various cellulose contents and manufactured by various molding methods, and is easier to handle since it is less likely to scatter than a powder.

[0016] <Cellulose powder> The cellulose powder of the present invention can be produced, for example, by using pulp derived from refined, highly pure cotton linters, wood, bamboo, bagasse, etc., and grinding this pulp in a grinder such as a knife mill, vertical roller mill, or jet mill to obtain powdered pulp as a raw material, and classifying the powder to obtain the desired average particle size.

[0017] The average particle size of the cellulose powder is 24 μm or less, preferably 20 μm or less, more preferably 18 μm or less. If the average particle size exceeds 24 μm, inflation molding may be difficult. If the average particle size is 24 μm or less, there will be no holes due to drawdown during extrusion, and it will be easier to accommodate fine structures during injection, so the resin composition will have excellent moldability and toughness.

[0018] The average particle size of the cellulose powder is 6 μm or more, preferably 8 μm or more, more preferably 10 μm or more. If the average particle size is less than 6 μm, the surface area of ​​the cellulose powder increases, so that the amount of the compatibilizer that covers it needs to be increased, and the physical properties of the molded product are poor. If the average particle size is 6 μm or more, the rigidity of the resin composition is excellent, and the bulkiness of the cellulose powder as a raw material is reduced, making it easier to manufacture the resin composition.

[0019] The "average particle size" refers to the 50% particle size (D50), and can be measured as the volume average particle size using a laser diffraction particle size distribution measuring device (Malvern dry particle size distribution meter, product name: MASTER SIZER 3000) or the like.

[0020] The cellulose powder may be a commercially available product, such as cellulose microfiber ARBOCEL (registered trademark) manufactured by Rettenmeyer Japan Co., Ltd., or powdered cellulose KC Flock (registered trademark) manufactured by Nippon Paper Industries Co., Ltd.

[0021] The amount of cellulose powder is 50 to 70 parts by mass, preferably 50.5 to 67 parts by mass, more preferably 51 to 65 parts by mass, and may be 60 to 65 parts by mass, when the total amount of the resin composition is 100 parts by mass. If the amount of cellulose powder is less than 50 parts by mass, the cellulose powder content of the molded product, which is the final product, is limited. If the amount of cellulose powder is more than 70 parts by mass, production becomes difficult.

[0022] <Maleic anhydride modified polyolefin> MA-PO functions as a compatibilizer, and when the resin composition contains MA-PO, the cellulose powder becomes more easily dispersed in the resin composition.

[0023] Examples of MA-PO include α-olefin-maleic anhydride copolymers, mixtures of α-olefin polymers and maleic anhydride, mixtures of α-olefins, α-olefin-maleic anhydride copolymers and maleic anhydride, etc. Examples of α-olefins include ethylene, propylene, etc.

[0024] The amount of MA-PO is 0.5 to 8 parts by mass, preferably 1 to 6 parts by mass, and may be 1.2 to 6 parts by mass, based on 100 parts by mass of the entire resin composition. If the amount of MA-PO is less than 0.5 parts by mass, the cellulose powder is not sufficiently compatible with the olefin elastomer or the low-density polyethylene (A) and aggregates, resulting in a decrease in dispersibility of the cellulose powder and a decrease in moldability. If the amount of MA-PO is more than 8 parts by mass, the strength and solvent resistance of the molded product decrease.

[0025] The melt viscosity of MA-PO is preferably 100 to 15,000 mPa s, and more preferably 200 to 5,000 mPa s. When the melt viscosity of MA-PO is 100 mPa s or more, the resin composition will have excellent moldability and toughness, and when it is 15,000 mPa s or less, the resin composition will have excellent rigidity.

[0026] The "melt viscosity" refers to the viscosity measured by a capillary rheometer.

[0027] The acid value of MA-PO is preferably 5 to 150 mgKOH / g, more preferably 30 to 100 mgKOH / g. When the acid value of MA-PO is 5 mgKOH / g or more, the resin composition has excellent moldability, and when it is 150 mgKOH / g or less, the resin composition has excellent appearance.

[0028] The "acid value" refers to a value measured by neutralization titration.

[0029] <Olefin elastomer> The olefin-based elastomer is a component that contributes to improving the moldability of the resin composition.

[0030] Specifically, for example, in inflation molding, the cellulose powder is not stretched at all during stretching. In order to improve the moldability of the resin composition, it is important that the resin components other than the cellulose powder follow the cellulose powder during stretching.

[0031] Compared with general thermoplastic resins, olefin-based elastomers have better conformity to cellulose powder during stretching. In other words, by including an olefin-based elastomer, the elongational viscosity of the resin composition during cooling (to about 90°C) after stretching is reduced. Thus, by including an olefin-based elastomer, the moldability of the resin composition is improved.

[0032] The olefin-based elastomer used in the present invention includes copolymers or homopolymers mainly composed of an olefin having 3 or more carbon atoms, and copolymers mainly composed of ethylene and an olefin having 3 or more carbon atoms.

[0033] More specifically, examples of the olefin elastomer include propylene-ethylene copolymer, ethylene-propylene-diene terpolymer, etc. The olefin elastomer may be used alone or in combination of two or more kinds.

[0034] Furthermore, olefin elastomers are generally composed of hard segments that govern basic physical properties such as mechanical properties, and soft segments that govern elasticity, which is a rubber-like property. Olefin elastomers whose hard segments consist of polypropylene are called propylene elastomers, and those whose hard segments consist of polyethylene are called ethylene elastomers. Examples of soft segments in olefin elastomers include EPDM, EPM, EBM, IIR, hydrogenated styrene butadiene rubber (HSBR), NBR, and acrylic rubber (ACM).

[0035] In addition, from the viewpoints of excellent moldability, particularly low-temperature moldability, of the resin composition as well as excellent toughness, a copolymer mainly composed of propylene (for example, the above-mentioned "propylene-ethylene copolymer") or a propylene-based elastomer which is a homopolymer of propylene is preferred.

[0036] In the case of a propylene-based elastomer, the content of propylene units relative to all units is preferably 70% by mass to 95% by mass, more preferably 80% by mass to 90% by mass. If the content of propylene units, which are hard segments, is 70% by mass or more, strength is improved, and excellent moldability is obtained, and if it is 95% by mass or less, excellent stretchability is obtained due to the elasticity of the soft segments.

[0037] The amount of the olefin-based elastomer is 5 to 20 parts by mass, preferably 5.5 to 18 parts by mass, more preferably 6 to 10 parts by mass, and may be 6.5 to 10 parts by mass, when the total amount of the resin composition is 100 parts by mass. If the amount of the olefin-based elastomer is less than 5 parts by mass, sufficient low-temperature moldability cannot be obtained. If the amount of the olefin-based elastomer is more than 20 parts by mass, molding is possible, but the solvent resistance is poor, making it difficult to use for food packaging, etc., and other uses of the molded product are limited.

[0038] When a propylene-based elastomer is used as the olefin-based elastomer, the melt mass flow rate (MFR) of the propylene-based elastomer is, for example, preferably 1 to 30 g / 10 min, more preferably 3 to 16 g / 10 min, and is not intended to be limited thereto. If the MFR of the propylene-based elastomer is 1 g / 10 min or more, the resin composition will have excellent moldability and rigidity, and if it is 30 g / 10 min or less, the resin composition will have excellent moldability and toughness.

[0039] The above-mentioned melt mass flow rate is obtained by measurement in accordance with the provisions of JIS K 7210-1:2014, and the measurement conditions for the propylene-based elastomer in this application are the conditions described in the Examples.

[0040] The MFR can be measured under conditions of a temperature of 230°C and a load of 2.16 kg for general polypropylene-based resins, and a temperature of 190°C and a load of 2.16 kg for general polyethylene-based resins.

[0041] The melting point of the propylene-based elastomer is preferably 50 to 160° C., and more preferably 50 to 80° C. If the melting point of the propylene-based elastomer is 50° C. or higher, the toughness of the resin composition is superior, and if it is 160° C. or lower, the rigidity of the resin composition is superior.

[0042] The "melting point" refers to the melting initiation temperature on a DSC chart in a differential scanning calorimeter (DSC).

[0043] <Low density polyethylene (A)> As the low-density polyethylene (A), low-density polyethylene (LDPE), which is a homopolymer of ethylene, linear low-density polyethylene (LLDPE), ultra-low-density polyethylene (ULDPE), etc. can be used, and one of these may be used alone, or two or more of them may be used in combination.

[0044] As the low-density polyethylene (A), low-density polyethylene (density: 0.900 to 0.930 g / cm 3 Such low-density polyethylene does not easily lose flexibility even when combined with cellulose powder to form a resin composition, and is easily compatible with elastomers, improving the production stability of the resin composition.

[0045] Furthermore, when linear low-density polyethylene (LLDPE) or low-density polyethylene obtained by a metallocene catalyst is used as the low-density polyethylene (A), the sliding properties are improved, and therefore the resin composition of the present invention is particularly suitable for molded products having a screw shape, such as container lids that are frequently opened and closed.

[0046] The amount of the low-density polyethylene (A) is 12 to 45 parts by mass, preferably 14 to 40 parts by mass, more preferably 20 to 38 parts by mass, and may be 20 to 30 parts by mass, or may be 20 to 27 parts by mass, when the total amount of the resin composition is 100 parts by mass. When the amount of the low-density polyethylene (A) is less than 12 parts by mass, the resin composition becomes hard and brittle, and the proportion of cellulose powder increases, making production difficult. When the amount of the low-density polyethylene (A) is more than 30 parts by mass, the proportion of cellulose powder in the resin composition decreases.

[0047] <Other ingredients> The resin composition may further contain other components other than the above-mentioned cellulose powder, maleic anhydride modified polyolefin, olefin-based elastomer, and polyethylene-based resin, as necessary, such as additives such as stabilizers, antioxidants, lubricants, antistatic agents, and colorants.

[0048] The amount of other components in the resin composition is preferably 0 parts by mass or more and less than 7 parts by mass, and more preferably 0 parts by mass or more and less than 6 parts by mass, when the entire resin composition is taken as 100 parts by mass.

[0049] In addition, the resin composition preferably contains a lubricant as another component. When the average particle size of the cellulose powder is large, the surface roughness of the strands of the resin composition tends to occur, making granulation difficult. By adding a lubricant to the resin composition, the occurrence of surface roughness in the strands is suppressed, and granulation properties are improved. The lubricant is not particularly limited, but specific examples include stearic acid, zinc stearate, barium stearate, calcium stearate, and the like.

[0050] When the resin composition contains a lubricant, the amount of the lubricant in the resin composition is preferably 2 parts by mass or more and less than 7 parts by mass, preferably 2.5 parts by mass or more and less than 6 parts by mass, and particularly preferably 3 parts by mass or more and less than 5.4 parts by mass, when the entire resin composition is taken as 100 parts by mass. In the composition that preferably contains a lubricant, if the amount of the lubricant is 2 parts by mass or more and less than 7 parts by mass, it is possible to maintain other physical properties (e.g., toughness) while obtaining the effect of improving granulation, so that the effect of the lubricant can be fully utilized. If the amount of the lubricant is less than 2 parts by mass, the effect may not be fully exerted. If the amount of the lubricant is 7 parts by mass or more, the cellulose powder may be easily aggregated, and the physical properties (e.g., toughness) of the resin composition and the molded product containing it may tend to decrease.

[0051] ≪Molded products≫ The molded article according to the present invention can be obtained by subjecting the resin compound obtained by mixing the above-mentioned resin composition with a low-density polyethylene (B) for dilution and various optional additives, etc., to various molding processes.

[0052] The resin compound may be obtained, for example, by dry-blending the above-mentioned resin composition with the low-density polyethylene (B) and the like before feeding them into a molding machine, or by feeding them into the molding machine in a desired order and kneading them in the molding machine. In this specification, the term "resin compound" is a concept that includes both the above-mentioned dry-blended state and the state kneaded in the molding machine.

[0053] <Low density polyethylene (B)> Examples of the low-density polyethylene (B) include low-density polyethylene (LDPE), which is a homopolymer of ethylene, linear low-density polyethylene (LLDPE), and ultra-low-density polyethylene (ULDPE), and these may be used alone or in combination of two or more. The low-density polyethylene (B) is advantageous in terms of cost, and by diluting the resin composition with the low-density polyethylene (B), the molded product has excellent cold resistance and waterproof properties and can prevent moisture absorption by cellulose.

[0054] From the viewpoint of contributing to improving the manufacturing stability of molded products, low-density polyethylene (B) is low-density polyethylene (density: 0.900 to 0.930 g / cm 3 ) may also be used.

[0055] Furthermore, when linear low-density polyethylene (LLDPE) is used as the low-density polyethylene (B), the molded product has good elongation and better physical properties such as tear strength.

[0056] When linear low-density polyethylene (LLDPE) or low-density polyethylene obtained by a metallocene catalyst is used as the low-density polyethylene (B), the sliding properties are improved. Therefore, it is particularly suitable for screw-shaped molded products such as container lids that are frequently opened and closed.

[0057] The low-density polyethylene (B) may be the same as or different from the low-density polyethylene (A). From the viewpoint of obtaining excellent physical properties of a molded product while ensuring excellent moldability of the resin composition and the resin compound, it is preferable to use LDPE as the low-density polyethylene (A) and LLDPE as the low-density polyethylene (B).

[0058] The amount of the low-density polyethylene (B) when the entire molded article is taken as 100 parts by mass is not intended to be limited, but is preferably 10 parts by mass or more and 60 parts by mass or less, more preferably 40 parts by mass or more and 57 parts by mass or less, and particularly preferably 45 parts by mass or more and 55 parts by mass or less. If the amount of the low-density polyethylene (B) is less than 10 parts by mass, the cellulose powder content of the molded article becomes excessive, and moldability decreases. If the amount of the low-density polyethylene (B) is more than 60 parts by mass, the cellulose powder content of the molded article decreases, and the effect of reducing the amount of synthetic resin used is reduced. However, it is not excluded that the amount of the low-density polyethylene (B) in the molded article is more than 60 parts by mass.

[0059] <Cellulose powder content in molded products> The content of cellulose powder in the molded article is preferably from 10% by mass to 40% by mass, and more preferably from 15% by mass to 35% by mass.

[0060] <Application> The uses of the molded article of the present invention are not intended to be limited, but specific examples include containers for medicines and cosmetics that store highly fluid substances such as liquids and creams, tableware such as cups, plates, forks, and spoons, outer bags for packaging sanitary products such as diapers, films for shopping bags, garbage bags, and various other daily necessities and industrial products.

[0061] <<Method for producing resin composition and molded article>> Next, an example of a method for producing the resin composition and the molded article of the present invention will be described.

[0062] <Method of producing resin composition> First, cellulose powder and MA-PO are mixed in a predetermined mixing ratio, and then the resulting mixture is mixed with low-density polyethylene (A), an olefin-based elastomer, and any other components in predetermined mixing ratios. The mixture is melt-kneaded at a predetermined temperature K1 in a corotating twin-screw extruder equipped with a strand die and extruded into strands. The extruded mixture is cut to obtain pellets of the resin composition.

[0063] The mixing method may be a dry mixing method using a Super Mixer, a Henschel Mixer or the like.

[0064] Furthermore, the resin composition of the present invention has excellent low-temperature moldability, and the temperature during production of the resin composition, i.e., the above-mentioned predetermined temperature K1, can be, for example, 150°C or lower, preferably 140°C or higher and 150°C or lower, although this is not intended to be limiting. Note that the temperature during production of the resin composition in this disclosure refers to the cylinder temperature set in the extruder, and when the cylinder temperature can be set at multiple locations, all of the set values ​​correspond to the above-mentioned predetermined temperature K1. Therefore, for example, when the cylinder temperature can be set at N locations, the N set values ​​of the cylinder temperature are K11, K12, ..., K1 NThen, if the predetermined temperature K1 is within the above temperature range, N set values ​​K11, K12, ..., K1 N All of the above temperatures are within the above range.

[0065] <Method of manufacturing molded products> The molded article of the present invention can be obtained by molding a resin compound comprising the above-mentioned pellets, a low-density polyethylene (B) for dilution, and optional additives, using a generally known molding method.

[0066] For example, when injection molding is used as the molding method, the resin compound is injection molded at a predetermined temperature K2.

[0067] Also, for example, when inflation molding is used as a molding method, the above-mentioned resin compound is melt-kneaded at a predetermined temperature K2 in a single-screw extruder, introduced into a circular die and extruded, while simultaneously blowing air into the compound to expand it into a film, and the film is wound up on a take-up roll to obtain the molded product of the present invention.

[0068] The resin compound has excellent low-temperature moldability, and the temperature during production of the molded product, i.e., the above-mentioned predetermined temperature K2, can be, for example, 160°C or less, preferably 140°C or more and 160°C or less, without any intention to be limited thereto. Note that the temperature during production of the molded product in this disclosure refers to the cylinder temperature set in the extruder, and when the cylinder temperature can be set at multiple locations, all the set values ​​correspond to the above-mentioned predetermined temperature K2. Therefore, for example, when the cylinder temperature can be set at N locations, the N set values ​​of the cylinder temperature are K21, K22, ..., K2 N Then, if the predetermined temperature K2 is within the above temperature range, N set values ​​K21, K22, ..., K2 N All of the above temperatures are within the above range. EXAMPLES

[0069] The present invention will be described below based on examples. Note that the present invention is not limited to these examples, and these examples can be modified or changed based on the spirit of the present invention, and they are not excluded from the scope of the present invention.

[0070] ≪Material≫ The materials used in this example are shown below. Note that MFR1 is a value at a temperature of 190°C and a load of 2.16 kg, in accordance with the JIS K 7210-1:2014 regulations, and MFR2 is a value at a temperature of 230°C and a load of 2.16 kg, in accordance with the JIS K 7210-1:2014 regulations. (1) Cellulose powder 1 (average particle size: 18 μm, manufactured by Rettenmeyer Japan Co., Ltd., product name: ARBOCEL (registered trademark) BE600-10TG) (2) Cellulose powder 2 (average particle size: 10 μm, manufactured by Rettenmeyer Japan Co., Ltd., product name: ARBOCEL (registered trademark) UFC100) (3) Cellulose powder 3 (average particle size: 30 μm, manufactured by Rettenmeyer Japan Co., Ltd., product name: ARBOCEL (registered trademark) BE600-30) The average particle size of each cellulose powder was measured using a laser diffraction particle size distribution measuring device (Malvern dry particle size distribution meter, product name: MASTER SIZER 3000). (4) Propylene-based elastomer 1 (propylene-ethylene copolymer, ethylene unit content: 16 mass%, MFR1: 1.4 g / 10 min, MFR2: 3 g / 10 min, melting point: 55° C., manufactured by ExxonMobil, trade name: Vistamaxx (registered trademark) 6102FL) (5) Propylene-based elastomer 2 (propylene-ethylene copolymer, ethylene unit content: 6% by mass, MFR2: 10,000 g to 100,000 g / 10 min (actual measurement is not possible, so a converted value based on melt viscosity is shown), melting point: 97°C, manufactured by ExxonMobil, product name: Vistamaxx (registered trademark) 8880) The MFR1 in a 2:1 mixture (mass ratio) of the propylene-based elastomer 1 and the propylene-based elastomer 2 was 6.4 g / 10 min (Examples 1 to 8, Comparative Example 2). Also, the MFR1 in a 1:1 mixture (mass ratio) of the propylene-based elastomer 1 and the propylene-based elastomer 2 was 15.4 g / 10 min (Example 9). (6) Low-density polyethylene-1 (low-density polyethylene, density: 0.922 g / cm 3 , MFR1: 2g / 10min, Lotte Chemical Co., Ltd., Product name: TITANLENE (registered trademark) LDF200YZ) (7) Low-density polyethylene-2 ​​(linear low-density polyethylene, density: 0.913 g / cm 3 , MFR1: 2g / 10min, manufactured by Prime Polymer Co., Ltd., product name: Evolue (registered trademark) SP1520) (8) MA-PO (olefin wax, α-olefin-maleic anhydride copolymer: 66.8% by mass, α-olefin polymer: 32.9% by mass, maleic anhydride: 0.3% by mass, melting point: 70 to 76°C, melt viscosity: 140 to 210 mPa s, acid value: 95 to 110 mgKOH / g, manufactured by Mitsubishi Chemical Corporation, trade name: Diacarna 30M) (9) Anti-dye agent (fatty acid metal salt additive, base polymer: low-density polyethylene (density: 0.9 g / cm 3 ), MFR1: 6.3g / 10min, masterbatch containing 10% by mass of magnesium 12-hydroxystearate, manufactured by Katsuta Kako Co., Ltd., product name: AP-600P) (10) Compatibilizing agent (hydrogenated styrene-based thermoplastic elastomer, manufactured by Asahi Kasei Corporation, product name: Tuftec (registered trademark) M1913) (11) Lubricant-1 (zinc stearate, manufactured by NOF Corporation, trade name: Zinc Stearate GP) (12) Lubricant-2 (zinc stearate, manufactured by Riken Vitamin Co., Ltd., trade name: Rikemal TG-12) (13) Antifoaming agent (master pellets containing 65% by mass of calcium oxide as an active ingredient and 35% by mass of LLDPE as a base polymer, manufactured by Ohmi Chemical Industry Co., Ltd., BELL-CML EM) <Examples 1 to 9, Comparative Examples 1 and 2> <Preparation of Resin Composition> According to the formulations shown in Table 1, resin compositions of Examples 1 to 9 and Comparative Examples 1 and 2 were prepared by the following procedures.

[0071] [Table 1]

[0072] First, cellulose powder and MA-PO were mixed in a super mixer to obtain a mixture. Next, the mixture obtained and the remaining raw materials (low-density polyethylene (A), propylene-based elastomer, and other materials) were melt-kneaded in a co-rotating twin-screw extruder at a molding temperature of 150°C and a screw rotation speed of 40 to 120 rpm, and extruded into strands with a diameter of 2 to 4 mm. The extruded mixture was then cut into pellets of the resin composition.

[0073] <Moldability evaluation 1: Strand condition evaluation> The state of the strand extruded by the co-rotating twin screw extruder during the production of pellets of the resin composition, i.e., the external shape and surface of the strand, was visually observed. The state of the strand was evaluated according to the following criteria. The results are shown in Table 1.

[0074] ○: No surface roughness △: Surface roughness is observed, but there is no problem with granulation. ×: Surface roughness is observed, and there are problems with granulation (strands are often torn off) <Production of Molded Products (Films)> The obtained pellets of the resin composition of Examples 1 to 9 and Comparative Examples 1 and 2, low-density polyethylene (B), and bubble inhibitor were dry-blended in the amounts shown in Table 1, and melt-kneaded in a single-screw extruder at a molding temperature of 160°C and a screw rotation speed of 60 rpm. The mixture was then introduced into a circular die and blown into a tube, after which it was cooled and solidified by air cooling, and wound up by a winder. The film had a width (width when the blown-inflation molded product was folded. That is, the molded product was molded into a cylindrical shape with a circumference of 200 mm) of 100 mm and a thickness of 70 μm. The screw specifications were full flight, L / D: 25, and C / R: 3.08.

[0075] <Moldability evaluation 2: Presence or absence of pinholes> The surface of the molded product was observed using a digital microscope (Keyence Digital Microscope, VHX-7000) to evaluate the presence or absence of pinholes. In detail, a test specimen measuring 10 cm in width and 30 cm in length was cut out from the molded product, and the surface was observed at a measurement magnification of 40x while manually moving the test specimen on the digital microscope stage. The entire surface, including the ends of the test specimen, was observed, and if pinholes were observed, it was rated as "present," and if no pinholes were observed, it was rated as "absent." The results are shown in Table 1.

[0076] Fig. 1 shows digital microscope images of the surfaces of the molded articles of Example 1 and Comparative Example 1. No pinholes were observed in the molded article of Example 1. Pinholes were observed in the molded article of Comparative Example 1, as indicated by the white arrows in Fig. 1.

[0077] <Moldability evaluation 3: Bubble stability during molding> The bubble stability during the production of the molded products was evaluated according to the following criteria. The results are shown in Table 1.

[0078] ○: It is possible to manufacture molded products with a stable width △: Width may be disturbed, but molding is possible ×: Bubble formation is insufficient, making it practically difficult to manufacture molded products. <Consideration> As shown in Table 1, the strand state was good (△ or ○) in the resin compositions of Examples 1 to 9, and no pinholes were observed in the molded products produced using the resin compositions, demonstrating excellent bubble stability during molding. In Examples 1 to 9, it is believed that the moldability was improved by the inclusion of a propylene-based elastomer in the resin compositions.

[0079] On the other hand, in the resin composition of Comparative Example 1, the strand state was rated as "good", but the molded product produced using the resin composition had pinholes, indicating poor bubble stability during molding. It is believed that the resin composition of Comparative Example 1 does not contain a propylene-based elastomer, and therefore other resin components are unable to fully follow the cellulose powder during stretching, resulting in the generation of pinholes.

[0080] In addition, the strand state of the resin composition of Comparative Example 2 was rated as x, and the molded product produced using the resin composition had many pinholes and insufficient bubble formation, making it difficult to produce a molded product that could actually be used in practice. The resin composition of Comparative Example 2 contains a propylene-based elastomer, but the average particle size of the cellulose powder is large. Therefore, even though the propylene-based elastomer is included, the cellulose powder cannot be completely followed up during stretching, resulting in many pinholes, i.e., molding is difficult. [Industrial Applicability]

[0081] As described above, the present invention is suitable for a resin composition containing cellulose powder and a molded article thereof.

Claims

1. A resin composition containing cellulose powder, When the entire resin composition is taken as 100 parts by mass, the resin composition contains 50 to 70 parts by mass of the cellulose powder, 0.5 to 8 parts by mass of a maleic anhydride-modified polyolefin, 5 to 20 parts by mass of an olefin-based elastomer, and 12 to 45 parts by mass of a low-density polyethylene (A), The resin composition, wherein the average particle diameter (D50) of the cellulose powder is 6 μm or more and 24 μm or less.

2. The resin composition according to claim 1 , wherein the low-density polyethylene (A) comprises a homopolymer of ethylene.

3. A molded article comprising the resin composition according to claim 1 or 2 and a low-density polyethylene (B).

4. The molded article according to claim 3 , wherein the low-density polyethylene (B) comprises a linear low-density polyethylene.

5. A method for producing the resin composition according to claim 1 or 2, comprising the steps of: The method for producing a resin composition, wherein the temperature during production of the resin composition is 150° C. or lower.

6. A method for producing the molded article according to claim 3, comprising the steps of: The method for producing a molded product, wherein the temperature during production of the molded product is 160° C. or lower.

Citation Information

Patent Citations

  • Manufacturing method for resin composition containing fine paper powder

    JP2013006411A

  • Fiber resin mixed composition film for bag, and method for producing same

    WO2022064772A1